Demand Atomization and the Erosion of Competitive Coherence: Strategic Implications of Algorithmic Personalization - Riza Saepul Millah (UDEX Institute, 2026)
Algorithmic personalization has been widely conceptualized as a performance-enhancing capability that improves targeting precision and customer alignment. However, its structural consequences for market organization and strategic stability remain under-theorized. This conceptual article advances a market-structure perspective by introducing the constructs of demand atomization and competitive coherence. It argues that increasing algorithmic personalization intensity reduces shared exposure across consumers, dispersing preferences into dynamically reconfigured micro-clusters. Simultaneously, reinforcement mechanisms embedded in digital platforms may concentrate transactional outcomes among highly visible actors. This dual dynamic—fragmentation in preference formation alongside concentration in transaction distribution—creates structural pressures that erode competitive coherence, defined as the firm’s ability to maintain integrative strategic alignment across heterogeneous market contexts. The analysis proposes non-linear effects of personalization intensity and identifies privacy salience and firm size as critical boundary conditions. Small and medium-sized enterprises are theorized to face amplified vulnerability due to limited orchestration capacity. The framework reframes personalization from a tactical optimization tool to a market-structuring force with long-term strategic implications.